A Superluminal Formalism for Majorana-like Lepton - Thuan, Vo Van (Communications in Physics, 2009)
This work deals with the nature of Majorana particles by applying the time-like formalism of the superluminal Lorentz transformation (SLT). It is proposed that along with the SLT of the space-time coordinates, the Dirac equation should be treated simultaneously by a Majorana-like representation to be invariant. This formalism leads to a natural understanding of Majorana physics.